Neoadjuvant Chemoradiotherapy Does Not Contribute to Worse Survival in Pathological Node-Negative Rectal Cancer - Huang, Yong; Wei, Wei; Wang, Zhenguang; Liang, Tao; Tian, Shuyun; Fu, Guangshun (Frontiers in Oncology, 2021)
Purpose: The prognostic significance of ypN0 rectal cancer with comparison to pN0 disease still remains poorly defined. This study aimed to compare the prognosis of ypN0 and pN0 rectal cancer. Methods: Eligible patients were identified from the SEER18 registries research database (the latest data up to date was on April 15, 2019). Propensity score (PS) matching was usually performed to reduce the imbalance and potential confounding that were introduced by inherent differences between the groups. The cause-specific survival (CSS) was analyzed to evaluate the prognostic prediction of ypN0 and pN0 groups using the Kaplan–Meier method with the log-rank test. Cox proportional hazard model was also used to identify independent prognostic variables. Results: In total, 26,832 patients diagnosed with pN0 or ypN0 rectal cancer were confirmed as the final cohort, including 7,237 (27.0%) patients with radiation and 19,595 (73.0%) patients without radiation prior to surgery. The median follow-up time was up to 81 months. After adjusting for other prognostic factors, neoadjuvant radiotherapy was not an independent prognostic variable of CSS (HR = 1.100, 95%CI = 0.957–1.265, P = 0.180, using pN0 group as the reference). Conclusions: ypN0 rectal cancer was strongly associated with worse pathological diagnoses compared with pN0 rectal cancer, contributing to worse oncologic outcomes. However, the receipt of neoadjuvant chemoradiotherapy was not an independent prognostic factor of worse prognosis in pathological node-negative patients. Our study could give guidance to the treatment of ypN0 rectal cancer.